Aerosol-Processed Nanomaterials for Antimicrobial Air Filtration - Bae, Gwi-Nam; Jung, Jae Hee (AMER SCIENTIFIC PUBLISHERS, 2016)
Health-care products are a dominant application of various nanotechnologies. Silver nanoparticles are widely used in commercial products requiring antimicrobial activity. Due to the limitations of wet processing in nanotechnology applications, dry aerosol processes have been developed for indoor antimicrobial air filtration. In this work, various aerosol processes for the synthesis or generation of nanomaterials, natural-product nanoparticles, and hybrid nanoparticles are reviewed. Key aerosol processes and the morphologies of various antimicrobial nanoparticles generated using a variety of systems or deposited on filter fibers are introduced.
Keywords: SOPHORA-FLAVESCENS NANOPARTICLES; NATURAL-PRODUCT NANOPARTICLES; AIRBORNE SILVER NANOPARTICLES; BACILLUS-SUBTILIS BIOAEROSOLS; SMALL CERAMIC HEATER; ESCHERICHIA-COLI; ANTIBACTERIAL; INACTIVATION; FILTERS; BACTERIA